The Structure of Homoserine Dehydrogenase from Saccharomyces cerevisiae - DeLaBerre, Byron (My University, 2000)
The core of this work is the structural determination of the enzyme homoserine dehydrogenase from Saccharomyces cerevisiae . The structure has been determined in three different states of ligation: apo form, in a binary form complexed with nicotinamide cofactor, and in a ternary form complexed with both L-homoserine and a nicotinamide cofactor analogue. The structures were determined by X-ray diffraction studies to resolutions of 2.3, 2.3, and 2.6 Å, respectively. Due to problems with non-isomorphism, the measured amplitudes were phased from a single heavy atom derivative. Data averaging about a local two-fold axis (non-crystallographic symmetry) was used in combination with other density modification techniques to resolve the phase ambiguity problem arising from single isomorphous replacement. Because traditional techniques failed to locate the axis, a novel technique for locating the symmetry axis was devised. The fold of the catalytic/substrate binding portion of the structure establishes homoserine dehydrogenase as a unique dehydrogenase. The ternary complex reveals that the amino acid substrate binds to the enzyme in an unusual manner. Site directed mutagenesis data based upon the structure validates the selection of active site residues. Furthermore, the combination of residues employed for catalysis of the hydride transfer suggests that the bound form may be a gem -diol form. Reaction mechanisms in both the forward and reverse directions are proposed. This is the first structural determination of homoserine dehydrogenase. A comparison of the Saccharomyces cerevisiae homoserine dehydrogenase primary sequence with sequences from other homoserine dehydrogenases reveals that the fold of this enzyme is conserved across species. The structure explains the effect monovalent cations have upon the enzyme, how it is affected by an inhibitory compound and suggests a possible mechanism for allosteric control.
Keywords: Biochemistry; Biochemistry